RECONSTRUCTING TRADITIONAL SYMBOLS: FEMINIST SEMIOTIC TRANSLATION IN CONTEMPORARY FUZHOU SOFTWOOD CARVING JEWELRY DESIGN - Lin, Tong; Sirisuk, Mateta (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the contemporary reinterpretation of traditional cultural symbols in Fuzhou softwood carving jewelry from a feminist perspective. As an important form of Chinese intangible cultural heritage, Fuzhou softwood carving has historically incorporated symbolic systems derived from Song Dynasty aesthetics, particularly botanical and animal motifs associated with moral discipline, social hierarchy, and gender norms. However, limited research has explored how these traditional symbols can be reconstructed to reflect contemporary female subjectivity and identity within modern design contexts. Using a qualitative and practice-oriented methodology, the study combines field investigation, iconographic analysis, cultural semiotics, and feminist theory to investigate the transformation of symbolic meanings in contemporary jewelry design. Fieldwork conducted in Fuzhou between 2024 and 2025 was combined with iconographic and semiotic analysis of representative Song Dynasty artworks. The research further adopts a “research through design” approach to semiotically translate traditional symbolic elements into contemporary feminist wearable forms. The findings demonstrate that traditional motifs such as the lotus, bamboo, orchid, and crane possess significant semiotic flexibility and can be reconstructed through semantic, syntactic, and pragmatic transformation. Rather than functioning as symbols of female discipline and moral restraint, these motifs are reinterpreted as expressions of autonomy, resilience, self-growth, and spiritual subjectivity. The study also reveals that contemporary jewelry design provides an effective medium for activating intangible cultural heritage within everyday cultural practice. By integrating feminist reinterpretation with heritage design, this research contributes to the development of localized feminist design discourse in East Asian contexts and proposes a contemporary pathway for the living inheritance and cultural sustainability of traditional crafts.